Efektivitas Strategi Pembelajaran Terdiferensiasi terhadap Pemahaman Konsep Siswa pada Matematika Matriks - Abdul Mannan Qoffal; Sunismi (Mandalika Mathematics and Educations Journal, 2026)
Many students have difficulty understanding mathematical concepts because learning is still quite teacher-centred and does not pay attention to individual learning needs. Differentiated learning is seen as being able to overcome this problem by adjusting content and processes according to students' abilities and learning styles. This study aims to determine the effectiveness of differentiated learning in improving the mathematical concept understanding abilities of grade XI students at SMK Al Khozini Gondanglegi in the subject of matrices. This study used a quantitative method with a quasi-experimental design of the pretest and posttest control group type. The sample consisted of two classes, namely the experimental class with differentiated learning and the control class with conventional learning. Data were obtained from concept comprehension tests and analyzed using statistical tests. The results showed a significant increase in the experimental class with an average post-test score of 82.69 and an N-Gain of 0.57, which was higher than the control class with a post-test score of 68.42 and an N-Gain of 0.51. The t-test also showed a significant difference between the two classes (sig. 0.000 < 0.05). Thus, differentiated learning proved to be more effective than conventional learning in improving students' mathematical concept understanding of matrix material.